2020
DOI: 10.1371/journal.pone.0244269
|View full text |Cite
|
Sign up to set email alerts
|

Time to recovery and its predictors among adults hospitalized with COVID-19: A prospective cohort study in Ethiopia

Abstract: Background Various factors may determine the duration of viral shedding (the time from infection to viral RNA-negative conversion or recovery) in COVID-19 patients. Understanding the average duration of recovery and its predictors is crucial in formulating preventive measures and optimizing treatment options. Therefore, evidence showing the duration of recovery from COVID-19 in different contexts and settings is necessary for tailoring appropriate treatment and prevention measures. This study aimed to investig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
37
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(53 citation statements)
references
References 27 publications
10
37
1
Order By: Relevance
“…This study pointed out that the median time to recovery from SARS COV-2 was 18 days. This is similar to the studies done in Eka Kotebe General Hospital, Ethiopia in which viral clearance lasted for 19 days [ 9 ] and 16 days [ 8 ]. This might be due to relative similarity in care and treatment given for the patients in both study areas.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…This study pointed out that the median time to recovery from SARS COV-2 was 18 days. This is similar to the studies done in Eka Kotebe General Hospital, Ethiopia in which viral clearance lasted for 19 days [ 9 ] and 16 days [ 8 ]. This might be due to relative similarity in care and treatment given for the patients in both study areas.…”
Section: Discussionsupporting
confidence: 89%
“…A study conducted in treatment center found in Ethiopia showed that, the rate of prognosis from COVID-19 for asymptomatic cases was higher when compared to symptomatic COVID-19 cases, and this study reported the average recovery time of 16 days [ 8 ]. Another study conducted in Kotebe treatment center of Ethiopia revealed the media time to recovery from COVID-19 was 19 days and it ranges from 2–71 days [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…As the body of literature concerning the coronavirus disease 2019 (COVID-19) expands, the pathophysiology and clinical manifestations of acute COVID-19 have become relatively common knowledge. Recovery times from COVID-19 drastically differ between patients and are highly dependent on the presence or absence of various risk factors that contribute to disease severity, such as age, body mass index, and underlying comorbidities ( 1 , 2 , 3 ). Although the clinical hallmarks are well-described, many symptoms are known to carry over into the recovery period, even after the acute phase has subsided.…”
Section: Introductionmentioning
confidence: 99%
“…9 Abrahim et al, showed in their study that those participants without comorbidities recovered more quickly than those with at least one comorbidity. 10 Trump et al, in their study reported hypertension as one of the factors which causes delay of viral clearance and exacerbates airway hyperinflammation in patients with COVID-19. 11…”
Section: Comorbiditiesmentioning
confidence: 97%